2016
DOI: 10.1016/j.drudis.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of glycosylation analysis and control: an integrated approach to producing optimal and consistent therapeutic drugs

Abstract: Glycosylation of therapeutic proteins has a profound impact on their safety and efficacy. Many factors shape the glycosylation of biotherapeutics, ranging from expression systems and cell culture processes to downstream purification strategies. Various analytical technologies have been developed to address questions concerning different aspects of glycosylation. Informatics tools are also crucial for a systematic understanding of the glycosylation processes. Hence, an integrated approach is required to harness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
164
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 238 publications
2
164
0
3
Order By: Relevance
“…As for the sialylated oligosaccharides, there are two kinds of sialic acid, including the mouse-type N-glycolyneuraminic acid (NGNA) and the human-type N-acetylneuraminic acid (NANA). Previously study has demonstrated that NGNA has an immunogenic risk to patients, while NANA has low hypersensitivity reactions 45 . Our recombinant mAb contained only NANA glycan without NGNA, which is the normal human-type sialylation with low potential immunogenicity.…”
Section: Discussionmentioning
confidence: 98%
“…As for the sialylated oligosaccharides, there are two kinds of sialic acid, including the mouse-type N-glycolyneuraminic acid (NGNA) and the human-type N-acetylneuraminic acid (NANA). Previously study has demonstrated that NGNA has an immunogenic risk to patients, while NANA has low hypersensitivity reactions 45 . Our recombinant mAb contained only NANA glycan without NGNA, which is the normal human-type sialylation with low potential immunogenicity.…”
Section: Discussionmentioning
confidence: 98%
“…Non-fucosylated therapeutic antibodies exhibit 50 to 1,000-fold higher efficacy than their fucosylated counterparts 65 due, in most cases, to enhanced ADCC activity 68 . Given the abundance of research efforts in this area, it is no surprise that many have concluded that glycosylation is one of the main areas requiring development 69 to improve efficacy 70 and safety 10,70 of next generation therapeutics 61 . Hence, the control of glycosylation of recombinant therapeutic molecules expressed in non-human systems is decisive 71 .…”
Section: Glycosylationmentioning
confidence: 99%
“…There are several excellent reviews focusing on the glycosylation analysis of therapeutic glycoproteins in detail [58][59][60][61][62][63]. N-glycosylation analysis of therapeutic proteins can be performed at three different levels (intact protein, glycopeptide, and released glycans), as depicted in Figure 3 [64]. Intact glycoproteins can be analyzed by mass spectrometry (MS) via direct infusion or coupling with separation techniques, such as liquid chromatography (LC)-MS or capillary electrophoresis (CE)-MS [65,66].…”
Section: Analytical Methods To Track N-glycosylation Patternsmentioning
confidence: 99%
“…The bottom-level analysis supports the in-depth microheterogeneity characterization of glycans. Reproduced, with permission, from [64]. For each point of the GU range, the RMP mean and its standard deviation (SD) is calculated to determine the lower and upper tolerance limits.…”
Section: András Guttmanmentioning
confidence: 99%